FROM THE DIONISIAN RITUALS TO THE CANDOMBLé RITUALS: THE BODY THAT DANCES. (Fiep Bulletin - online, 2015)
This study has the purpose of analyzing the existent relations between the old Greece's dionisian rituals and the contemporary candomblé rituals, above all in what refers to the body that dances in these manifestations. By means of bibliographical research it became possible to identify the liner category of the dionisian's rituals, confronting them with the original categories of the candomblé rituals, starting from investigations developed with the orixás dances on Brazil (LARA, 1999). Looking for answer the guiding question which crosses approaches between these rituals, the study points to coincidences among the dionisian dances and the orixás dances, showed by the establishment of the sacred time-space, by the sacrifices and offerings, by the trance and by the body in ecstasy state, fomenting reflections around the cultural combinations that line contemporary corporal praxis and that constitute themselves in education and knowledge sources.
Keywords: dionisian dances; orixás dances; rituals.